Biomechanical Analysis - Marshall, R. N.; Elliott, B. C.
Reprint with the permission of Blackwell Science Asia from Bloomfield, Tricker & Fitch, Science and Medicine in Sport. Biomechanical analysis is the evaluation of technique, whether in sports, industry or everyday life. Methods of analysis used in biomechanics vary from those requiring expensive and complex equipment to techniques utilizing little else than an acute eye and an understanding of the mechanics of the movement. The previous chapter discussed loads on (or in) the body, the movements which cause them, and their relationship to injury and performance in sport. This chapter will outline methods for determining those body motions and loads, as well as procedures commonly used to assess athletic performance. Analysis methods in biomechanics may be classified under three general areas, namely subjective, objective and predictive techniques. Most coaches and para-medical professionals use a variety of subjective evaluation techniques during their normal interaction with athletes or patients. They watch a subject, for example, to determine whether there are any gross abnormalities in the range of movement at a joint during walking. Objective techniques in biomechanics refer to the collection, measurement and evaluation of data from the activity of interest. Thus, the gait clinician may use a device to measure the instantaneous angle or the actual range of motion of the knee-joint of a patient, in order to evaluate progress in a rehabilitation program. Similarly, a coach may measure the forces a high jumper exerts on the ground during the take-off by using a force platform to determine the effect of a change in approach velocity. Predictive techniques attempt to answer the "What if...?" questions. For example, what effect would reducing the moment of inertia of a belowknee prosthesis have on the swing phase of an amputee`s gait?